One‐Pot Green Synthesis of Nitrogen‐Doped Carbon Quantum Dots for Cell Nucleus Labeling and Copper(II) Detection. Issue 22 (18th October 2017) - Ci, Jiliang; Tian, Ye; Kuga, Shigenori; Niu, Zhongwei; Wu, Min; Huang, Yong
Abstract: The doping of nitrogen into carbon quantum dots is vitally important for improved fluorescence performance. However, the synthesis of nitrogen‐doped carbon quantum dots (N‐CQDs) is usually conducted under strong acid and high temperature, which results in environmental pollution and energy consumption. Herein, the N‐CQDs were prepared by a mild one‐pot hydrothermal process. The hydrothermal reaction temperature was adjusted to control the particle size, nitrogen/carbon atomic ratio, and quantum yield. The products were water soluble with a narrow particle size distribution and good dispersion stability over a wide pH range. The N‐CQDs could penetrate into the HeLa cell nucleus without any further functionalization. Moreover, the fluorescence of N‐CQDs could be selectively quenched by Cu 2+, which suggested applications for the detection of Cu 2+ in human plasma. Abstract : Delivering doped dots to nuclei : A new method for the synthesis of nitrogen‐doped carbon quantum dots (N‐CQDs) through a mild one‐pot hydrothermal process is reported (see figure). The N‐CQDs could penetrate into the HeLa cell nucleus without any further functionalization. Moreover, the fluorescence of N‐CQDs could be selectively quenched by Cu 2+, which suggested applications for the detection of Cu 2+ in human plasma.